LIP-PRINTS – EVIDENCE LOST TO IMPERTINENCE - CHHIKARA, PANKAJ; SINGH, ABHISHEK (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Identity means determination of individuality of a person beyond doubt, based on physical characteristics unique to an individual. Article-6 of the Universal Declaration of Human Rights states that everyone has a right to identity as a person. The wrinkles and grooves on labial mucosa called form a characteristic pattern and the study of these is referred to as cheiloscopy. These are unique to an individual just like the fingerprints thus, hold the potential for identification purpose. This study was designed to evaluate lip-prints as a tool of forensic identification. Methods: The study was done in North Haryana on 1000 subjects aged between 15 and 25 years over a period of 2 years. Purposive sampling was done and subjects were asked to produce lip prints on bond paper, which were examined based on Suzuki and Tsuchihashi classification. Data obtained were analyzed using Student’s t-test. Results: It was found that no two individuals had similar lip prints. Type I pattern was most common followed by Type II whereas Type V was least common. Conclusion: However, till date, no reliable system with repeatability has been developed for studying lip-prints especially to remove observer bias. Nor any comprehensive studies are available comparing lip-prints in live and dead subjects to authenticate their forensic identification potential, raising question at forethought and purpose of practical application of research in the field of cheiloscopy.